CD58 reshapes the immunosuppressive microenvironment in gliomas through PD-L1 upregulation - Gou, Siqi; Zhao, Pengfei; Zong, Lei; Yu, Daihua; Liu, Wei; Zuo, Weichen; Wang, Juanhong; Wei, Wei (Frontiers in Oncology, 2025)
BackgroundCluster of Differentiation 58 (CD58), a critical immune regulator, is implicated in tumor immune evasion, yet its role in remodeling the immunosuppressive microenvironment of gliomas and regulating programmed death-ligand 1 (PD-L1) remains unclear. This study aimed to elucidate the clinical and mechanistic significance of CD58 in gliomas.MethodsThis study integrated bioinformatics analysis with in vitro validation. First, CD58 expression patterns, immunorelevance, prognostic significance, and clinical associations were evaluated using transcriptome data from TCGA (33 cancers, n=10,535) and CGGA (glioma, n=1,018). The immunomodulatory role of CD58 across tumors was assessed by comparing immune checkpoint molecules, chemokines, chemokine receptors, and immunoregulatory factors. ESTIMATE and CIBERSORT algorithms characterized the tumor immune microenvironment. CD58-related signaling pathways were identified through functional enrichment analysis (GO, KEGG, GSEA). In vitro, CD58 was knocked down in U87MG and LN229 glioma cells. Functional assays and protein expression validation were performed. Key cytokine levels (CCL5, CXCL9, CXCL10) secreted into conditioned media were quantified by ELISA to determine factors involved in CD58-mediated immune microenvironment remodeling.ResultsIn high-grade gliomas, the expression of CD58 was significantly increased, and it showed statistical differences in relation to clinical pathological indicators. Pan-cancer analysis revealed that CD58 was associated with key immune regulatory factors, including PD-L1, chemokines (CCL5, CXCL9, CXCL10). In vitro experiments demonstrated that knockdown of CD58 in glioma cells significantly inhibited proliferation, migration, and invasion, while enhancing the adhesion of T cells to glioma cells. Moreover, silencing of CD58 reduced the expression of PD-L1 and Vimentin, upregulated ICAM-1, and promoted the secretion of chemokines CCL5, CXCL9, and CXCL10.ConclusionsCD58 drives glioma progression by upregulating PD-L1 and reshaping the tumor microenvironment toward immunosuppression. It serves as an independent prognostic biomarker and a potential therapeutic target. Targeting the CD58-PD-L1 axis may enhance immunotherapy efficacy in gliomas.